Face to face: finding justice for my murdered twin brother - Dawson, Nick (Icon Books, 2025)
When his identical twin brother Simon was kicked to death, all Nick Dawson felt for the killers was hatred. Struggling in a world where his mirror image had vanished, he came to realise there was only one way to stop the torture - acceptance. Travelling to the absolute limits of personal darkness, Nick came face to face with his brother's killers. Now a champion of restorative justice, Nick heads behind bars, asking hardened criminals to change, to think of their victims, to make amends. In 'Face To Face' he takes us with him on a journey into this hidden and unpredictable world